2019
DOI: 10.1080/2162402x.2019.1577125
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of urothelial carcinoma through targeted type I interferon-mediated immune activation

Abstract: Type I interferon (IFN-I) has potent anti-tumor effects against urothelial carcinoma (UC) and may be an alternative treatment option for patients who do not respond to Bacillus Calmette-Guerin. However, the mechanisms that mediate the IFN-I-stimulated immune responses against UC have yet to be elucidated. Herein, we evaluated the anti-tumor mechanisms of IFN-I in UC in human patients and in mice. Patient tumors from a Phase I clinical trial with adenoviral interferon-α (Ad-IFNα/Syn3) showed increased expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
(80 reference statements)
2
16
0
Order By: Relevance
“…The same report was noted for polyinosinic:polycytidylic acid (poly(I:C)), a TLR3 agonist, also in combination with BCG in models of BCa [192,193]. Moreover, poly(I:C) treatment was efficient to enhance the anti-PD-1 response in a NMIBC model [193]. These results indicate that TLR agonists could be further investigated for the treatment of BCa to complement or replace BCG in NMIBC, or to improve ICIs in advanced BCa.…”
Section: Toll-like Receptor (Tlr) Agonistssupporting
confidence: 62%
See 1 more Smart Citation
“…The same report was noted for polyinosinic:polycytidylic acid (poly(I:C)), a TLR3 agonist, also in combination with BCG in models of BCa [192,193]. Moreover, poly(I:C) treatment was efficient to enhance the anti-PD-1 response in a NMIBC model [193]. These results indicate that TLR agonists could be further investigated for the treatment of BCa to complement or replace BCG in NMIBC, or to improve ICIs in advanced BCa.…”
Section: Toll-like Receptor (Tlr) Agonistssupporting
confidence: 62%
“…A clinical study on NMIBC patients indicated that a TLR7 agonist, in combination with BCG, induced a significant increase of cytokines in the urine of patients and increased clinical responses [191]. The same report was noted for polyinosinic:polycytidylic acid (poly(I:C)), a TLR3 agonist, also in combination with BCG in models of BCa [192,193]. Moreover, poly(I:C) treatment was efficient to enhance the anti-PD-1 response in a NMIBC model [193].…”
Section: Toll-like Receptor (Tlr) Agonistsmentioning
confidence: 65%
“…A primary goal of this study was to determine whether the antitumor efficacy of BCG in urothelial cancer models could be enhanced by engineering excess production of the STING agonist, c-di-AMP. In light of studies showing elevated Type I IFN and NF-κB-mediated antitumor host immune responses in NMIBC patients who respond to BCG [55][56][57] , we reasoned that adding STING agonist overexpression to traditional BCG might further increase these favorable immune parameters. c-di-AMP is a STING agonist produced naturally in low levels by BCG (where it serves as a second messenger signaling molecule in microbial physiology), that is closely related to the natural human STING ligand, cGAMP 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…A recently completed phase 3 clinical trial demonstrated that rAd-IFNα/Syn3 monotherapy had a complete response rate of 53.4% at 3 mo and 24.3% at 12 mo among 103 patients with carinoma in situ containing BCG-unresponsive disease [8] . In preclinical and clinical correlative studies, tumor-infiltrating lymphocytes, particularly CD8 + lymphocytes, increased after treatment [9] . Oncolytic adenovirus CG0070 also had antitumor activity in a cohort of bladder cancer patients unsuccessfully treated with BCG [10] .…”
mentioning
confidence: 99%
“…To truly achieve synergy with CPI, combination agents capable of recruiting [8]. In preclinical and clinical correlative studies, tumor-infiltrating lymphocytes, particularly CD8 + lymphocytes, increased after treatment [9]. Oncolytic adenovirus CG0070 also had antitumor activity in a cohort of bladder cancer patients unsuccessfully treated with BCG [10].…”
mentioning
confidence: 99%